Hemodynamic Differences in Intracranial Aneurysms before and after Rupture - Cornelissen, B.M.W. (AJNR Am J Neuroradiol, 2015)
BACKGROUND AND PURPOSE: Rupture risk of intracranial aneurysms may depend on hemodynamic characteristics. This has been assessed by comparing hemodynamic data of ruptured and unruptured aneurysms. However, aneurysm geometry may change before, during, or just after rupture; this difference causes potential changes in hemodynamics. We assessed changes in hemodynamics in a series of intracranial aneurysms, by using 3D imaging before and after rupture. MATERIALS AND METHODS: For 9 aneurysms in 9 patients, we used MRA, CTA, and 3D rotational angiography before and after rupture to generate geometric models of the aneurysm and perianeurysmal vasculature. Intra-aneurysmal hemodynamics were simulated by using computational fluid dynamics. Two neuroradiologists qualitatively assessed flow complexity, flow stability, inflow concentration, and flow impingement in consensus, by using flow-velocity streamlines and wall shear stress distributions. RESULTS: Hemodynamics changed in 6 of the 9 aneurysms. The median time between imaging before and after rupture was 678 days (range, 14–1461 days) in these 6 cases, compared with 151 days (range, 34–183 days) in the 3 cases with unaltered hemodynamics. Changes were observed for flow complexity (n = 3), flow stability (n = 3), inflow concentration (n = 2), and region of flow impingement (n = 3). These changes were in all instances associated with aneurysm displacement due to rupture-related hematomas, growth, or newly formed lobulations. CONCLUSIONS: Hemodynamic characteristics of intracranial aneurysms can be altered by geometric changes before, during, or just after rupture. Associations of hemodynamic characteristics with aneurysm rupture obtained from case-control studies comparing ruptured with unruptured aneurysms should therefore be interpreted with caution.